2016
DOI: 10.21837/pmjournal.v14.i4.155
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Critical Success Factors of Public Private Partnership in the Delivery of Urban Infrastructure and Services

Abstract: The inability of the public sector to independently meet the increasing demand for infrastructure and services has prompted many governments to adopt Public-private partnership (PPP) as an alternative strategy. In worldwide practices, however, there are mixed results and controversy in the application of PPP model. The Public-private partnership has, for this reason, become an increasingly active research area mainly to establish the Critical Success Factors (CSFs) towards improving the PPP model. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Many researchers have sought to find commonalities among PSI projects that contributed to their success or failure. One approach that has been used widely, is finding the critical success factors (CSFs) that attempt to delineate the most crucial areas that are required to ensure management success [24].…”
Section: Success Factors Of Private Sector Involvement In Infrastructmentioning
confidence: 99%
“…Many researchers have sought to find commonalities among PSI projects that contributed to their success or failure. One approach that has been used widely, is finding the critical success factors (CSFs) that attempt to delineate the most crucial areas that are required to ensure management success [24].…”
Section: Success Factors Of Private Sector Involvement In Infrastructmentioning
confidence: 99%
“…Raising awareness about different waste management programs is envisaged to have positive effects. Also, proper education and public awareness at the grassroots level were also suggested to enhance management of solid waste as these were expected to generate environmental concern and formation of groups to safeguard environment (Sinthumule and Mkumbuzi, 2019;Muhammad, Sik, Johar and Sabri, 2016). In addition, studies have identified right perception of people towards waste management as a costless way of managing solid waste and the primary mechanism to promote public health.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Other critical success factors of PPPs also mentioned are the creation of a central PPP unit and a compatible regulatory framework, the development of national PPP policies and strategies and the standardization and transparency of the processes (Amović et al, 2020). However, it is argued that critical success factors are differentiated and depend on the type, location and time of the project (Muhammad et al, 2016) and better results are achieved in PPPs as long as the public sector bears the financial costs and the private sector retains the project management (Moszoro, 2010). It should not be overlooked that state institutions, the leadership skills of the parties, the clarity of technical specifications and contracts and the possibility of contractual amendments play an essential role (Landow & Ebdon, 2012).…”
Section: The Critical Success Factors Of Pppsmentioning
confidence: 99%